Gray whale southbound migration surveys 1967–2006: an integrated re-analysis - Laake, Jeffrey L.; Punt, Andre E. (J. Cetacean Res. Manage., 2023)
Between 1967 and 2007, 23 seasons of shore-based counts of the Eastern North Pacific (ENP) stock of gray whales (Eschrichtius robustus) were conducted throughout all or most of the southbound migration near Carmel, California. Population estimates have been derived from these surveys using a variety of techniques that were adapted as the data collection protocol evolved. The subsequent time series of estimates was used to evaluate trend and population status, resulting in the conclusion that the population was no longer endangered and had achieved its optimum sustainable population (OSP) level. We re-evaluated the data from all of the surveys using a common estimation procedure and an improved method for treatment of error in pod size and detection probability estimation. The newly derived abundance estimates between 1967 and 1987 were generally larger (–2.5% to 21%) than previous abundance estimates. However, the opposite was the case for survey years 1992 to 2006, with estimates declining from –4.9% to –29%. This pattern is largely explained by the differences in the correction for pod size bias, which occurred because the pod sizes in the calibration data over-represented pods of two or more whales and underrepresented single whales relative to the estimated true pod size distribution.